Involvement of TRPC1 in Nampt-induced cardiomyocyte hypertrophy through the activation of ER stress - Li, J.; Wu, W.; Zhao, M.; Liu, X. (Cellular and Molecular Biology, 2017)
Nicotinamide phosphoribosyltransferase (Nampt) is involved in the development of cardiac hypertrophy. Transient receptor potential canonical channel 1 (TRPC1) and endoplasmic reticulum stress (ER stress) are regarded as critical pathways in cardiac hypertrophy. Therefore, we hypothesizedthat TRPC1 might be associated with ER stress in Nampt-induced cardiac hypertrophy. CulturedH9c2cardiomyocyteswereexposed to Namptfor different timesand the expression of markers of cardiomyocyte hypertrophy and ER stress, as well as TRPC1 were detected. Moreover, specific TRPC1-shRNA (short hairpin RNA) expressing plasmid was transfected to knockdown TRPC1 expression before Nampt stimulation. Thapsigargin was used as an agonist and pravastatin was employed as an inhibitor of ER stress. The results demonstrated that exposure of H9c2 cells to 100 ng/mL Nampt for 24h, 48h or 72h significantly increased the expression of atrial natriuretic peptide (ANP), brain natriuretic peptide (BNP), markers of ER stress and TRPC1. The Nampt-induced expression of TRPC1 was attenuated by pre-treatment with pravastatin, whereas promoted by pre-treatment with thapsigargin. Furthermore, transfection of TRPC1-shRNA for 48h partially inhibited Nampt-induced expression of ER stress markers and BNP in H9c2 cells. Our data suggest that TRPC1 might play an important role in cardiomyocyte hypertrophy induced by Namptinan ER stress-dependent way.